Застосування тренінгу «нейрофідбек» для молоді з розлучених родин - KORNACKA-SKWARA, Elżbieta; POKROPIŃSKA, Agata; SKWARA, Andrzej (Studies in Comparative Education, 2014)
Статтю присвячено висвітленню особливостей застосування тренінгу «нейрофідбек» для молоді, яка перебуває під впливом родинного стресу, викликаного розлученням батьків. «Нейрофідбек» виконується за допомогою техніки, яка полягає на механізмі зворотного зв’язку з використанням енцефалографії. Самі записи полягають у реєструванні біоелектричного стану мозку, що визначається за допомогою електродів, прикріплених до шкіри голови за чітко визначеною счемою. Статья посвящена рассмотрению особенностей применения тренинга «нейрофидбек» для молодежи, которая находится под влиянием семейного стресса, вызванного разводом родителей. «Нейрофидбек» выполняется с помощью техники, которая состоит на механизме обратной связи с использованием энцефалографии. Сами записи состоят в регистрировании биоэлектрического состояния мозга, определяется с помощью электродов, прикрепленных к коже головы по четко определенной чем. The article is devoted to the peculiarities of using neurofeedback training for children subject to family stress caused by parents’ divorse. The family stress is presented as the disfunctioning of particular family members as well as the family as a system. The stress is characterised as a lasting process, thus it is a longitude cause for non-adequate self-esteem, emotional problems and problems with socializing. The training is performed with the aid of the appliance based on the feedback mechanism using encephalography. The records register bioeletric state of brain conducted by electrodes fastened to the head in particular places. The cases described in the article have proved the positive effect of the approach to reduce family stress which is visible through the changes in the brain waves shwn in the pictures.